Baby's first bites: Association between observed maternal feeding behavior and infant vegetable intake and liking. (1st October 2021) - van Vliet, M.S.; Mesman, J.; Schultink, J.M.; de Vries, J.H.M.; Vereijken, C.M.J.L.; Rippe, R.C.A.; van der Veek, S.M.C.
Abstract: Positive experiences with the introduction of solid food in infancy may lead to positive associations with feeding in both parent and infant. During this transitional period, parental feeding behavior and infant eating behavior might mutually reinforce each other. A feeding style that is found to be associated with positive child eating behavior, is sensitive feeding. In the present study we tested bidirectional prospective relations between mother and infant behavior in a cross-lagged model using observations of two feeds on two consecutive days on which the first bites of solid food were offered. The sample consisted of 246 first-time mothers and their infants, whose feeding interactions were videotaped during two home visits. Maternal sensitive feeding behavior (consisting of responsiveness to child feeding cues, general sensitivity and non-intrusiveness) and maternal positive and negative affect were coded. In addition, infant vegetable intake was weighed and vegetable liking was reported by mother. Results showed at least some stability of maternal feeding behavior and infant vegetable intake and liking from the first to the second feed. In addition, during the second feed maternal sensitive feeding and positive affect were associated with infant vegetable intake ( r =.34 and r= .14) and liking ( r =.33 and r= .39). These associations were mostly absent during the first feed. Finally, infant vegetable liking during the first feed positively predicted maternal sensitive feeding behavior during the second feed ( β =.25), suggesting that the infant's first response might influence maternal behavior. Taken together, mother and infant seem more attuned during the second feed than during the first feed. Future studies might include multiple observations over a longer time period, or micro-coding. Such insights can inform prevention programs focusing on optimizing feeding experiences during the weaning period.